2020
DOI: 10.3390/ijms21186973
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Nrf2 Signaling in Obesity and Insulin Resistance

Abstract: Obesity, a metabolic disorder characterized by excessive accumulation of adipose tissue, has globally become an increasingly prevalent disease. Extensive studies have been conducted to elucidate the underlying mechanism of the development of obesity. In particular, the close association of inflammation and oxidative stress with obesity has become increasingly evident. Obesity has been shown to exhibit augmented levels of circulating proinflammatory cytokines, which have been associated with the activation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 106 publications
1
58
0
Order By: Relevance
“…Prolonged activation of NRF2 may also result in metabolic changes as NADPH-generating enzymes are targets of NRF2. Therefore, NRF2 acts as a direct link between redox homeostasis and energy metabolism [ 137 ]. NRF2 tightly controls GSH biosynthesis by regulating the expression of two GCL subunits, which catalyses the rate-limiting step of GSH biosynthesis, namely the reaction of glutamate with cysteine [ 138 ].…”
Section: The Antioxidant Effects Of Insulinmentioning
confidence: 99%
“…Prolonged activation of NRF2 may also result in metabolic changes as NADPH-generating enzymes are targets of NRF2. Therefore, NRF2 acts as a direct link between redox homeostasis and energy metabolism [ 137 ]. NRF2 tightly controls GSH biosynthesis by regulating the expression of two GCL subunits, which catalyses the rate-limiting step of GSH biosynthesis, namely the reaction of glutamate with cysteine [ 138 ].…”
Section: The Antioxidant Effects Of Insulinmentioning
confidence: 99%
“…A recent study has demonstrated that the inhibition of Nrf2 signalling could significantly promote the incidence of type I diabetes mellitus, and, on the other hand, its reactivation reduces oxidative stress in pancreatic β-cells [ 143 ]. At the same time, the absence of Nrf2 protects from insulin resistance in long-term high-fat diet feeding by decreasing adipose tissue inflammation [ 144 , 145 ].…”
Section: Nrf2 Activation As a Strategy For Covid-19 Treatmentmentioning
confidence: 99%
“…Recently, it was described that Nrf2 plays a role in controlling adipogenesis [ 73 , 81 , 82 , 83 , 84 , 85 , 86 ]. Several studies have shown that mice lacking Nrf2 can be protected from high fat diet induced obesity despite similar food intake [ 81 , 82 , 87 , 88 ].…”
Section: The Role Of Nrf2 In Energy Expenditurementioning
confidence: 99%